Performances e o brincar como instrumentos para a construção do inédito viável no Programa Digitmed - Silva, Sarah Bento dos Santos (2024)
The objective of this research is to analyze the performances and play activities carried out in the Digitmed Program, related to the planning, event, and evaluation of the first meeting of 2017. The aim is to observe whether and how these activities contributed to the construction of the Viable Unheard of (Freire, 2019) and the consequent decoloniality of education. This work is grounded in the theoreticalmethodological axes of the studies of Vygotsky ([1930] 2007), Magalhães (2011), Newman and Holzman (2011), Van Oers (2013), Liberali et al. (2015) and Freire (2019), which emphasize the dialectic of human action on the environment, transforming it and being transformed by it, through decapsulating (Liberali et al., 2015) and decolonial methodologies. The data from the analyzed event were produced and collected through video recordings conducted in the PUC Auditorium and adjacent rooms. This thesis focuses on descriptions of performances and the Play, in order to understand the possible realization of the Viable Unheard, through the critical, collective and collaborative construction of resources and instruments for the transposition of limit-situations. The analysis procedures involved categories of Play based on rules, imaginative situations, adult participation and participation of others; in the Decoloniality of being, knowing, doing and power, as well as in Argumentation for Collaboration. The results showed that a teaching proposal made through Play and performances promotes the decoloniality of being, learning, living, and doing because it rescues humanity and frees the oppressed subjects, bringing the possibility of propelling them towards the construction of an equitable, just reality made of Viable Unheard